Pengaruh Gender Diversity Dan Green Accounting Terhadap Pengungkapan CSR Pada Perusahaan LQ45 Tahun 2015-2022 - Pratama, Andino; Yuniarti, Rina; Junaidi, Ahmad (Politeknik Ganesha Medan, 2024)
The aim of the research is to determine the effect of gender diversity and green accounting on CSR disclosure in LQ45 companies from 2015 to 2022. This research is included in the quantitative research category. The company population that is the focus of this research is the LQ45 companies listed on the Indonesia Stock Exchange between 2015 and 2022. There are 45 companies included in this research population. The total number of samples used was 9 companies with a total of 72 observations, which were selected based on the purposive sampling method. Gender diversity as measured by dummy variables and green accounting as measured by PROPER are independent variables in this research. The control variable, displayed by company size, is measured using size. What is meant by the dependent variable is to reveal the company's CSR which is measured using GRI 4 guidelines. Data collection is carried out using the documentation method. The data used comes from secondary sources obtained through annual reports and company sustainability reports which can be accessed via the website www.idx.co.id and the official websites of each company. The testing technique used is the panel data regression method. Eviews 12 is software used to process data in testing research samples. In data testing, the probability methods used include descriptive statistical analysis, model selection test, classical assumption test, and hypothesis testing.